Interpretation of the Decision of the Standing Committee of the National People's Congress of China to Abolish the Bad Habit of Consuming Wildlife Mindlessly - Jiwen Chang (Universitat Autonoma de Barcelona. Facultat de Dret, 2020)
In order to eliminate the risk of potential disease spreading between people and wildlife, and to safeguard public health security of the society, as well as to maintain the ecological balance, the Standing Committee of the National People's Congress of China passed the decision to abolish the bad habit of consuming wildlife mindlessly in February 2020, which stipulated the scope of the fasting, measures of punishment, scope of edible livestock and poultry, and the special conditions and approval measures of non-edible utilization of wild animals, etc. The “Decision” reflects the practical and realistic legislative attitude: it not only eliminates the bad habits, but also provides the provisions of special conditions for captive breeding, which safeguard the basic stability of the economy. The method of combining Blacklist and Whitelist is adopted to delimit the boundary between illegal and legal. The whole chain of legal norms is constructed, which stipulated the applicable or suggested applicable legal liabilities for illegal acts and served as the “talons” of the law that brought it into play.